La communauté de pratique comme outil de formation pour mieux tenir compte du stress lié aux évaluations sommatives. Étude auprès d’enseignants du secondaire en Suisse - Alexandre Mabilon (Recherches en Éducation)
This paper looks at how supporting communities of practice of secondary school teachers can lead them to rethink their assessment practices, taking into account issues relating to the stress experienced by pupils who are not taking part in summative assessments. A series of meetings with professionals highlighted the practices adopted and contested, with a view to drawing up a reference framework of practices that would be meaningful and applicable locally. This approach has led to the implementation of co-constructed assessment practices that support learning and are sufficiently significant to be integrated into the professional culture, both individually and collectively.